Global Analysis of the Mechanical Properties of Organic Crystals. Issue 10 (3rd February 2022) - Karothu, Durga Prasad; Mahmoud Halabi, Jad; Ahmed, Ejaz; Ferreira, Rodrigo; Spackman, Peter R.; Spackman, Mark A.; Naumov, Panče
Abstract: Organic crystals, although widely studied, have not been considered nascent candidate materials in engineering design. Here we summarize the mechanical properties of organic crystals that have been reported over the past three decades, and we establish a global mechanical property profile that can be used to predict and identify mechanically robust organic crystals. Being composed of light elements, organic crystals populate a narrow region in the mechanical property–density space between soft, disordered organic materials and stiff, ordered materials. Two subsets of extraordinarily stiff and hard organic crystalline materials were identified and rationalized by the normalized number density, strength, and directionality of their intermolecular interactions. We conclude that future lightweight, soft, all‐organic components in devices should capitalize on the greatest asset of organic single crystals—namely, the combination of long‐range structural order and softness. Abstract : An extensive analysis of the mechanical properties of organic crystals has determined the limits of their mechanical performance as a separate class of engineering materials. This Minireview also explores the reasons for the softness of organic crystals.